Exerting control over the acyloin reaction. - Donohoe, T; Jahanshahi, A; Tucker, M; Bhatti, F; Roslan, I; Kabeshov, M; Wrigley, G (2011)
A synthetic method for conducting the acyloin reaction using electron transfer in solution is reported. By linking two esters via their oxygen atoms, it was possible to perform crossed acyloin reactions between two different ester functionalities and display a high degree of preference for an intramolecular coupling process.